Analysis and experiment of a bio-inspired flyable micro flapping wing rotor - Guo, Shijun; Li, Hao; Zhou, C.; Zhang, Y. L.; He, Y.; Wu, Jianghao (Elsevier, 2018)
Inspired by insect flapping wings, a novel flapping wing rotor (FWR) has been developed for micro aerial vehicle (MAV) application. The FWR combines flapping with rotary kinematics of motions to achieve high agility and efficiency of flight. To demonstrate the feasibility of FWR flight and its potential MAV application, an extensive and comprehensive study has been performed. The study includes design, analysis, manufacture, experimental and flight test of a flyable micro FWR model of only 2.6 gm weight. By experiment, the FWR kinematic motion and aerodynamic lift were measured using high speed camera and load cells. Within a range of input power, the difference between the measured aerodynamic force and the analytical results by a quasi-steady model was found to be within 3.1%–15.7%. It is noted that the FWR aeroelastic effect plays a significant role to obtain an ideal large angle of attack especially in up-stroke and enhance the FWR performance. Further analysis of the unsteady aerodynamic characteristics has been carried out based on the detailed airflow field of the FWR in a flapping cycle by CFD method. A successful vertical take-off and short hovering flight of the micro FWR model has been achieved for the first time in the research field. The flight test demonstrates the FWR feasibility and its unique feature of flight dynamics and stability for the first time. These characteristics have also been simulated by using ADAMS software interfaced with the aerodynamic model.
Keywords: Bioinspired flapping wing; Flyable micro FWR; Aeroelastic effect; Flight simulation